Arabic Verbal Communication Among Malaysian Taxi Drivers At KLIA: Contexts, Grammatical Structures, and Learning Needs - Musling, Mohd Nizwan; Mohamed, Yuslina (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigates Arabic verbal communication among Malaysian taxi drivers at Kuala Lumpur International Airport (KLIA), focusing on communicative contexts, grammatical structures, and learning needs within the Tourism Taxi Ambassadors program. Anchored in Hutchinson and Waters’ (1987) framework of necessities, lacks, and wants, the study aims to (i) identify real-life situations where communication in Arabic occurs between drivers and Arab tourists, (ii) determine the core vocabulary and grammatical structures required for effective interaction, and (iii) explore the drivers’ preferred methods for language acquisition. A qualitative approach was adopted, involving focused group interviews with six experienced Malaysian taxi drivers from AIRPORT LIMO (M) SDN BHD. Data were coded and analyzed using ATLAS.ti 7.1.4. Findings revealed 24 recurring communicative situations that span three primary functions: social (e.g., greetings), professional (e.g., providing directions or services), and promotional (e.g., introducing tourist attractions). While drivers possess limited Arabic proficiency, their communication needs demand specific lexical and grammatical competence, particularly in functional sentence patterns commonly used in tourism discourse. The study further identified six preferred learning strategies, including mobile-assisted tools and situational learning materials, reflecting professional requirements and individual learning preferences. This research offers practical insights for designing Arabic training modules tailored to taxi drivers' linguistic realities and learning styles. It contributes to the broader field of Arabic for Specific Purposes (ASP) and workplace-based language instruction.